Relationship between Diet and Acne - Kristina Sihaloho; Diah Mira Indramaya (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2016)
Background: Acne is a disorder of pilosebasea unit, that mostly affect an adolesecent, caused by hormonal changing. Dietary is one factor that was thought to induce acne. But the association  between diet and acne are still controversial.  Purpose: Review the role of  some diets for acne Review: Acne is multifactorial disease, whereas diet is one of many factors that excarcerbate acne.  Some dietaries are thought have some roles in acne, including carbohidrate, milk, chocolate, fatty acid, zinc-iodine, vitamin A, and antioxidant. Some research has proved the relationship between diets and acne but there are still few limitations. Conclusion: Relationship between diets and acne still need more research with better methods.  Key words: acne, diet, glicemic index.